ICT and school transformation: an empirical study on the perception of principals in the Klang Valley area on the Malaysian smart school - Hussin, Husnayati; Suhaimi, Mohd Adam; Abang Bawi, Zakiah (UUM Press, 2004)
Being one of the flagship applications in the Multimedia Super Corridor(MSC), the success of the Malaysian Smart School is very important to the country. Principals, being one of the stakeholders of the Smart Schools, are the drivers of the educational reinvention at the school level. This study aims to investigate the perception of principals towards the implementation of Malaysian Smart Schools. A survey was done using questionnares. The respondents were principals of pilot Malaysian Smart Schools and ordinary schools in the Federal Territory of Kuala Lumpur. Data from 40 respondents were analyzed. The findings revealed that the principals participating in the study have a positive perception towards the implementation of the Malaysian Smart School. The principals' understanding and knowledge on the Smart School concept has a significant relationship with their perception. On the other hand, their skills in IT and computer usage, length of service and tenures as principals have no significant relationship with their perception on Smart School implementation. The study provides some insights on the perception of school leadership in building ICT-capable schools in the context of a developing country.